Double trouble sum

Calculus Level pending

Find n = 0 k = 0 n k ( 2 n 2 k 1 ) ! ! ( k + 1 ) ! ( 2 + 2 n 2 k ) ! ! \sum_{n=0}^{\infty} \sum_{k=0}^n \frac{k(2n-2k-1)!!}{(k+1)!(2+2n-2k)!!}


This problem, taken from Romanian Mathematical Magazine , was proposed by Professor Daniel Sitaru, Romania.


The answer is 1.0000.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Naren Bhandari
Mar 21, 2020

Here I wish to share my solution. :)

Here we write 2 n 2 k 1 = 2 M 3 2n-2k-1 =2M-3 and 2 n 2 k + 2 = 2 M 2n-2k+2=2M and Ω = k = 0 k = 0 n k ( k + 1 ) ! ( 2 ( n k 1 ) + 1 ) ! ! ( 2 ( n k + 1 ) ) ! ! = k = 0 M = 1 k k ( k + 1 ) ! ( 2 M 3 ) ! ! ( 2 M ) ! ! \Omega = \sum_{k=0}^{\infty}\sum_{k=0}^n\frac{k}{(k+1)!}\frac{(2(n-k-1)+1)!!}{(2(n-k+1))!!}=\sum_{k=0}^{\infty} \sum_{M=1}^{k}\frac{k}{(k+1)!} \frac{(2M-3)!!}{(2M)!!} further M = 1 k = M 1 k ( k + 1 ) ! ( 2 M 3 ) ! ! ( 2 M ) ! ! = ( k = 0 k ( k + 1 ) ! ) ( M = 0 ( 2 M 1 ) ! ! ( 2 ( M + 1 ) ) ! ! ) \sum_{M=1}^{\infty}\sum_{k=M-1}^{\infty}\frac{k}{(k+1)!}\frac{(2M-3)!!}{(2M)!!} =\left(\sum_{k=0}^{\infty}\frac{k}{(k+1)!}\right)\left(\sum_{M=0}^{\infty}\frac{(2M-1)!!}{(2(M+1))!!}\right) Note that the former sum is Telescoping sum and latter sum can be expressed in terms of factorial as lim N k = 1 N k ( k + 1 ) ! ( M = 0 ( 2 M 1 ) ! ! ( 2 ( M + 1 ) ) ! ! ) = lim N ( 1 1 ( N + 1 ) ! ) β ( M ) = β ( M ) \lim_{N\to\infty}\sum_{k=1}^{N} \frac{k}{(k+1)!}\left(\sum_{M=0}^{\infty}\frac{(2M-1)!!}{(2(M+1))!!}\right) =\lim_{N\to\infty} \left(1-\frac{1}{(N+1)!}\right) \beta (M)=\beta(M) and β ( M ) = M = 0 ( 2 M 1 ) ! ! ( 2 M ) ! ! = M = 0 ( 2 M ) ! 2 M M ! ( 2 M + 1 ( M + 1 ) ! ) = 1 2 M = 0 1 4 M ( M + 1 ) ( 2 M M ) \beta(M)=\sum_{M=0}^{\infty} \frac{(2M-1)!!}{(2M)!!} =\sum_{M=0}^{\infty}\frac{(2M)!}{2^M M! ( 2^{M+1}( M+1)!)}=\frac{1}{2}\sum_{M=0}^{\infty}\frac{1}{4^M(M+1)}{2M \choose M} Recall the Generating function for central binomial coefficient a nd hence on integrating with respect to x x from 0 0 to 1 4 \frac{1}{4} we get 0 1 4 1 1 4 x = 0 1 4 n = 0 ( 2 M M ) x M 2 β ( M ) = 0 1 4 4 1 4 x = 2 \int_0^{\frac{1}{4}}\frac{1}{\sqrt{1-4x}}=\int_0^{\frac{1}{4}}\sum_{n=0}^{\infty}{ 2M \choose M} x^M \Rightarrow 2\beta (M) = \int_0^{\frac{1}{4}}\frac{4}{\sqrt{1-4x}}=2 Therefore β ( M ) = 1 \beta(M)=1 and hence is the answer.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...